2019
DOI: 10.1111/1471-0528.15818
|View full text |Cite
|
Sign up to set email alerts
|

Severe maternal morbidity during delivery hospitalisation in a large international administrative database, 2008–2013: a retrospective cohort

Abstract: Objective This study utilized the Dr. Foster Global Comparators database to identify pregnancy complications and associated risk factors that led to severe maternal morbidity during delivery hospitalisations in large university hospitals based in the USA, Australia, and England. Design Retrospective cohort. Setting Births in the USA, England and Australia from 2008 to 2013. Sample Data from delivery hospitalisations between 2008 and 2013 were examined using the Dr. Foster Global Comparators database. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…The findings from this study are consistent with a study investigating SMM hospitalizations in the United States, England, and Australia from 2008 to 2013, which found that advanced maternal age, substance use, hypertension, and diabetes were strongly associated with SMM in all three countries (Lipkind et al, 2019). Rates of women with chronic health conditions such as hypertension, cardiac disease, and diabetes in the United States are increasing (Hirshberg & Srinivas, 2017).…”
Section: Discussion Principal Findingssupporting
confidence: 89%
“…The findings from this study are consistent with a study investigating SMM hospitalizations in the United States, England, and Australia from 2008 to 2013, which found that advanced maternal age, substance use, hypertension, and diabetes were strongly associated with SMM in all three countries (Lipkind et al, 2019). Rates of women with chronic health conditions such as hypertension, cardiac disease, and diabetes in the United States are increasing (Hirshberg & Srinivas, 2017).…”
Section: Discussion Principal Findingssupporting
confidence: 89%
“…The highest proportion of near misses was seen among studies that used other non-WHO based criteria (30.5 per 1000 births, 95% CI 28.1, 33.0, 23 studies) ( Table 3 , Table S3). These criteria included those developed prior to the WHO criteria [25] , [26] , [27] and those using other common near miss criteria, such as the CDC-endorsed surveillance algorithm [28] . Interestingly, the proportion of near misses in studies that used The WHO criteria ( Figure 3 , Table 3 , Table S3) were much lower at 14.8 per 1000 births (95% CI 13.3 - 16.3, 32 studies).…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] Severe maternal morbidity affects an estimated 15.8/1000 US births per year. 5 Unlike other similar Organization for Economic Cooperation and Development (OECD) countries, maternal mortality is not decreasing and there are marked racial inequities. 6 Black and Indigenous women in the United States are far more likely to die as a result of pregnancy than are white women.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the US maternal mortality rate is more than double that of other countries with similar levels of economic development 2–4 . Severe maternal morbidity affects an estimated 15.8/1000 US births per year 5 . Unlike other similar Organization for Economic Cooperation and Development (OECD) countries, maternal mortality is not decreasing and there are marked racial inequities 6 .…”
Section: Introductionmentioning
confidence: 99%